2016
DOI: 10.1140/epjc/s10052-016-4136-3
|View full text |Cite
|
Sign up to set email alerts
|

Higgs Starobinsky inflation

Abstract: In this paper we point out that Starobinsky inflation could be induced by quantum effects due to a large nonminimal coupling of the Higgs boson to the Ricci scalar. The Higgs Starobinsky mechanism provides a solution to issues attached to large Higgs field values in the early universe which in a metastable universe would not be a viable option. We verify explicitly that these large quantum corrections do not destabilize Starobinsky's potential.The idea that inflation may be due to degrees of freedom already pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 21 publications
(30 reference statements)
6
119
0
Order By: Relevance
“…[20,23,[41][42][43], while Refs. [21,44] have an opposite sign. Note that the sign convention of the Ricci tensor does not affect that of α 1 since the latter depends quadratically on the former.…”
Section: Renormalization Group Equation and Scalaronmentioning
confidence: 99%
“…[20,23,[41][42][43], while Refs. [21,44] have an opposite sign. Note that the sign convention of the Ricci tensor does not affect that of α 1 since the latter depends quadratically on the former.…”
Section: Renormalization Group Equation and Scalaronmentioning
confidence: 99%
“…While other types of gravitational couplings, such as αR 2 , can also play important role in inflationary dynamics (see e.g. [24,25]),…”
Section: Inflationary Dynamicsmentioning
confidence: 99%
“…The fimplaton condensate decays at Γ φ 0 →σσ H, giving 24) for the field value at the time of condensate decay. Here we used 25) which can be derived by using the fimplaton energy density, ρ φ 0 = λ φ Φ 4 0 /4, in the Friedmann equation 3H 2 M 2 P = ρ. Equating then the fimplaton energy density with the energy density of the heat bath, π 2 g * T 4 /30, at the time of the fimplaton decay gives…”
Section: Jhep09(2016)049mentioning
confidence: 99%
“…11 In principle, the SM Higgs should not be forgotten, and one can ask what is its effect on the inflationary dynamics. It can be shown that the presence of the Higgs alongside the R 2 term leads to multifield inflation in metric gravity, as recently studied in Refs [124][125][126][127][128][129][130][131][132]12.…”
mentioning
confidence: 90%